2016
DOI: 10.1111/jth.13389
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti‐domain 1‐β2glycoprotein I antibodies in the diagnosis and risk stratification of antiphospholipid syndrome

Abstract: To cite this article: de Craemer A-S, Musial J, Devreese KMJ. Role of anti-domain 1-b 2 glycoprotein I antibodies in the diagnosis and risk stratification of antiphospholipid syndrome. J Thromb Haemost 2016; 14: 1779-87. Essentials• Antibodies to domain 1 of b 2 glycoprotein I (aD1) are a subset of antiphospholipid antibodies.• We evaluated the added diagnostic value of an automated aD1 assay in antiphospholipid syndrome.• AD1 IgG correctly classifies patients at risk for thrombosis.• Agreement between aD1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 37 publications
(56 reference statements)
3
37
3
4
Order By: Relevance
“…Moreover, they found increasing titers of aD1 antibodies in a Chinese population with single-positive, double-positive and triplepositive antibody profiles, which we and others have confirmed in a Caucasian population [2,3]. The authors support earlier conclusions that aD1 antibodies have no additional diagnostic value [2], but detection of aD1 IgG could serve as a promising biomarker for the identification of patients at risk for thrombotic complications [3][4][5], especially in a Chinese population. They verified its value in diagnosis and risk stratification in patients with different ethnic/geographic backgrounds.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, they found increasing titers of aD1 antibodies in a Chinese population with single-positive, double-positive and triplepositive antibody profiles, which we and others have confirmed in a Caucasian population [2,3]. The authors support earlier conclusions that aD1 antibodies have no additional diagnostic value [2], but detection of aD1 IgG could serve as a promising biomarker for the identification of patients at risk for thrombotic complications [3][4][5], especially in a Chinese population. They verified its value in diagnosis and risk stratification in patients with different ethnic/geographic backgrounds.…”
supporting
confidence: 73%
“…In their study, the authors confirm the significant correlation between anti-b 2 GPI domain 1 (aD1) antibodies (detected with the QUANTA Flash assay; Inova Diagnostics, San Diego, CA, USA) and thrombotic complications in a broad study population (odds ratio [OR] 3.27, 95% confidence interval [CI] 1.59-6.71), in contrast to aD1-independent anti-ab 2 GPI (ab 2 GPI) antibodies, which are not significantly associated with clinical events (OR 1.37, 95% CI 0.57-3.28) [1]. Moreover, they found increasing titers of aD1 antibodies in a Chinese population with single-positive, double-positive and triplepositive antibody profiles, which we and others have confirmed in a Caucasian population [2,3]. The authors support earlier conclusions that aD1 antibodies have no additional diagnostic value [2], but detection of aD1 IgG could serve as a promising biomarker for the identification of patients at risk for thrombotic complications [3][4][5], especially in a Chinese population.…”
mentioning
confidence: 71%
“…Several studies with the CIA aD1 assay confirmed high odds ratios for thrombosis and the role of aD1 in risk stratification [41][42][43][44]. Correlating to the higher risk, aD1 IgG are mainly present in triple-positive patients, also showing higher levels [42,43]. A limited number of studies have evaluated whether the aD1 are independent risk factors for thrombosis, and showed that aD1 had no added value to the current aPL panel [42,45].…”
Section: Other Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Correlating to the higher risk, aD1 IgG are mainly present in triple-positive patients, also showing higher levels [42,43]. A limited number of studies have evaluated whether the aD1 are independent risk factors for thrombosis, and showed that aD1 had no added value to the current aPL panel [42,45]. So far, aD1 measured by the only available commercial assay should be considered as a confirmation of the higher thrombotic risk, rather than a candidate for replacement of the ab2GPI.…”
Section: Other Antiphospholipid Antibodiesmentioning
confidence: 99%
“…The anti domain I antibodies, which have been shown to correlate with thrombosis and obstetric complications are promising new candidates [2,26]. Using an automated anti-domain I assay, high titres with this assay was found to be associated with triple positive APS and thrombosis [29], however this testing did not add significant diagnostic value to the existing panel in a recent report.…”
Section: Patients To Be Tested For Apsmentioning
confidence: 94%